Selective Reduction of Halogenated Nitroarenes with Hydrazine Hydrate in the Presence of Pd/C - Li, Fang; Frett, Brendan; Li, Hong-yu (Synlett, 2014)
A large variety of halogenated nitroarenes have been selectively reduced with hydrazine hydrate in the presence of Pd/C to give the corresponding (halogenated) anilines in good yield.
Keywords: reduction; nitroarenes; hydrazine hydrate; palladium on carbon; aromatic amines; transfer hydrogenation